Identifikasi Perilaku Bullying Pada Siswa Kelas III Di SD Negeri Kadipiro 2 Bantul Yogyakarta : Bentuk Perilaku bullying pada siswa kelas III - Muhammad Amien; Heru Purnomo; Rian Nurizka (LPPM Universitas Widya Dharma, 2024)
This research aims to identify forms of bullying behavior in class III students at SD N Kadipiro 2 Kasih Bantul Yogyakarta. This study used descriptive qualitative method. The data collection techniques used in this research are observation, interviews and documentation. The subject criteria in this research were 3 students who had been perpetrators of bullying and 1 class III teacher at SD N Kadipiro 2. The analysis technique used was presenting research data and drawing conclusions from data analysis. This research explains that the forms of bullying behavior that occur at SD N Kadipiro 2 are verbal and relational bullying. Based on the research results, the forms of verbal bullying found were 1) calling friends with bad names, 2) mocking, 3) insulting, 4) slandering, 5) accusing, 6) threatening, and 7) encouraging and spreading bad news about the victim . and the forms of relational bullying found were 1) exclusion, 2) exclusion, 3) neglect and, 4) avoidance/avoidance.Keywords: Bullying, intimidation